METHAPHYSICS OF DEATH PENALTY - V. E. Gromov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The paper studies the problem of death penalty justifiableness in terms of democratic society from the metaphysical viewpoint. Philosophical argumentation to justify death penalty is proposed as opposed to the common idea of inhuman and uncivilized nature of court practice of sentencing to death. The essence of the study is not to rehabilitate law-based murder but to explain dialectic relation of the degrees of moral responsibility of criminals and society nourishing evildoers. The author believes that refusal from death penalty under the pretence of rule of humanism is just a liberal façade, plausible excuse for defective moral state of the society which, rejecting its own guiltiness share as for current disregards of the law, does not grow but downgrades proper human dignity. Methodology. The author applies an approach of dialectic reflection being guided by the perception of unity, relativeness and complementarity of evil and good striving to determine efficient way of resolving their contradictions in the context of moral progress of the society. Originality. Proposing philosophic approach to a death penalty problem instead of legal one, the author is not going to discuss the role of horrification, control or cruelty of the measure of restraint; moreover, he does not consider the issue of its efficiency or inefficiency. The author also does not concern vexation of mind of a criminal sentenced to life imprisonment for “humanitarian” reasons. The purpose of the author is to demonstrate that aim of the punishment is to achieve justice which becomes spiritual challenge and moral recompense not only for the criminal but for the whole society. Conclusions. Crime is first of all a problem of a society; thus, criminal behaviour of certain individuals should only be considered through a prism of moral state of the whole community. Attitude to a death penalty is the problem of spirituality and its dramatic sophistication. The author thinks that moral standards exclude any sentimental interpretation of humanism and mercy. Humanism is the imperative requiring both personal and social responsibility for the things humiliated in a victim and human dignity downtrodden in a criminal. Law-breaker cannot be liquidated without judicial safeguards as a dangerous animal. Severe punishment of the society adequately compensates a murderer his/her human dignity. As the society is guilty partially in the existing criminality, it accepts the fact of cruel punishment applied to redress an injustice.